Economic Evaluation of Management of Dementia Patients - A Systematic Literature Review - Sanjib Saha; Ulf-G. Gerdtham; Håkan Toresson; Lennart Minthon; Johan Jarl (Lund University, School of Economics and Management, Department of Economics, 2018)
Objective: The objective is to systematically review the literature on economic evaluations of the interventions for the management of dementia and Alzheimer patients in home, hospital or institutional care. Methods: A systematic search of published economic evaluation studies in English was conducted using specified key words in relevant databased and websites. Data extracted included methods and empirical evidence (costs, effects, incremental cost-effectiveness ratio) and we assessed if the conclusions made in terms of cost-effectiveness were supported by the reported evidence. The included studies were also assessed for reporting quality using the Consolidated Health Economic Evaluation Reporting Standards (CHEERS) checklist. Results: Twelve studies were identified and there was a considerable heterogeneity in methodological approaches, target populations, study time frames, and perspectives as well as types of interventions. Interventions for the management of dementia patients are in general, not cost-effective. Interventions at the community and home setting for managing both the dementia patients and caregivers on a large scale may have the potential to save societal resources. Conclusion: More effectiveness studies as well as good quality economic evaluations are required before implementation decisions on management strategies can be made based on cost-effectiveness.
Keywords: H43; I10; I18; 330; Dementia; nursing home care; community care; residential care; economic evaluation